PERLINDUNGAN HUKUM TERHADAP HAK KEKAYAAN INTELEKTUAL (HKI) DI INDONESIA - Suhaimi Suhaimi; Kurniawan Kurniawan; Roslaini Ramli; Enzus Tinianus; Dedy Yuliansyah (Prodi Ilmu Hukum, Universitas Teuku Umar, 2021)
In everyday life, whether we realize it or not, we will always come into contact with the use of Intellectual Property Rights (IPR) on the products we consume or use. In the current era of globalization, IPR has become a very important issue and has always received the attention of various parties, both national and international levels. IPR is the only right that is specifically granted to the inventor / creator, while other parties are prohibited from using the invention / creation. For this reason, IPRs need to be legally protected. The formulation of the problem in this research is what are the steps in providing legal protection for IPR in Indonesia and how is Indonesia's concern as a member of the WTO in providing legal protection for IPR. As a normative juridical research, to obtain data, literature research is carried out in order to obtain legal material, both primary, secondary and tertiary legal materials. The approach method used is the statutory approach, namely by examining the applicable legal provisions which are related to the issue of legal protection of IPR in Indonesia. In the legal protection of IPR, several routes can be taken, namely national, regional, European and international routes. As an effort to protect IPR, Indonesia has ratified several international conventions and harmonized several laws and regulations in the IPR sector. However, the legislation that has been produced should be supported in the form of law enforcement, so that it will have a positive impact on creators. Especially now that there are more and more practices of IPR violations, CD and VCD piracy, song or art piracy and so on. Likewise, violations in the field of brands that are rife with the development of online businesses such as Shopee, Lazada, Tokopedia, Bukalapak, JD.ID, OLX and others, both officially registered and unregistered.